2008
DOI: 10.1007/978-0-387-69080-3_34
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of SNP in Estrogen-metabolizing Enzymes for Ovarian, Endometrial, and Breast Cancers in Novosibirsk, Russia

Abstract: We estimated the frequency of CYP1A1, CYP1A2, CYP1B1, CYP19, and SULT1A1 allelic variants in a female population of the Novosibirsk district and their association with the elevated risk of breast (BC), ovarian (OC), and endometrial (EC) cancers. Significant differences (OR = 2.34, p = 0.0002) in the allele distributions for CYP1A1 M1 polymorphism between patients with BC (n = 118) and controls (n = 180) were found. No significant difference in both genotype and allele distributions for CYP1A1 polymorphisms in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 20 publications
0
31
1
1
Order By: Relevance
“…the Caucasian part of the study by Gulyaeva et al [36]. After the exclusion of this study the results remained practically unchanged, as the associations still did not reach significance.…”
Section: Ala119ser Polymorphismmentioning
confidence: 70%
See 1 more Smart Citation
“…the Caucasian part of the study by Gulyaeva et al [36]. After the exclusion of this study the results remained practically unchanged, as the associations still did not reach significance.…”
Section: Ala119ser Polymorphismmentioning
confidence: 70%
“…Concerning Arg48Gly polymorphism, 10 studies were eligible (11,321 cases and 13,379 controls) [9,22,23,[28][29][30][31][32][33]; 11 studies were eligible for Ala119Ser (10,715 cases and 11,678 controls) [9,22,23,28,31,[34][35][36][37][38]; 12 cases were eligible regarding Asn453Ser (11,630 cases and 14,053 controls) [22, 29-32, 35, 39-43].…”
Section: Eligible Studiesmentioning
confidence: 99%
“…14,[30][31][32][33] Findings have been inconsistent, however, showing no association for Chinese, 30 Caucasian 31 or American-African women; 31 a positive association for Russian women; 33 and an inverse association for a multiethnic group (Multiethnic Cohort Study). 14 In the present study, we found a significantly decreased risk among NJB with the CC genotype of CYP1A2*1F.…”
Section: Discussionmentioning
confidence: 99%
“…They did not find the significant association of SULT1A1 R213H polymorphism with breast cancer in the Europeans. Results of many subsequent epidemiologic studies were different or even contradictory [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The purpose of this meta-analysis study was to access the overall relationship between the SULT1A1 R213H polymorphism and breast cancer risk from the published case-control studies and to quantify the potential between-study heterogeneity.…”
Section: Introductionmentioning
confidence: 99%